The Implication of Constructivism Theory towards Communicative Language Teaching Practice - Emma Maemunah (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2012)
There are some schools or thought in teach my language spectally the second language such as behaviourism/structuralism, rationalism and constructivism. Each thought has certain features and characteristics. Besides, there are also methods used in teaching language, one of them is communication language teaching (CLT). This paper describes the characteristics of constructivism theory and communicative language teaching method and finds  out the implications of constructivism theory towards communicative language teaching practice. The result shows that there is a significant implication of the constructivism theory towards the communicative language practice.